Estudio energético del proceso de obtención de panela en dos variedades de Saccharum officinarum L. (caña de azúcar) en la Amazonía Ecuatoriana - Víctor González-Rivera; Michael José Albán-Galárraga; Juan González-Rivera; Irene Hidalgo-Guerrero (TecnoLógicas)
The Ecuadorian Amazon is a region where Saccharum officinarum L. is cultivated for panela production. Traditionally, this process relied on the use of firewood as an energy source for juice concentration. This practice generated an environmental impact and affected the quality of the final product. The objective of this research was to demonstrate the advantages of implementing new technologies in panela production. The methodology employed consisted of evaluating the energy process used in 36 panela factories in the Ecuadorian Amazon that used traditional methods with furnaces. The studyfocused on two cane varieties cultivated in the country: Puerto Rico and Limeña. The maturity index and physical characteristics of both varieties were evaluated. Additionally, a laboratory-scale trial was conducted where cane juice was concentrated usingsteam generated by boilers, with the aim of comparing the efficiency of this method with the traditional one. For each process, a mass and energy balance were performed. The results indicated that the average overall efficiency in the furnace system was 58,50 %, while in the boiler system it reached 83,50%. In conclusion, these results demonstrated that the use of boilers in panela production is significantly more energy efficient than the traditional furnace method, with a positive increase of 25 % in overall efficiency. This technological improvement not only decreases the environmental impacts associated with panela production but also represents an opportunity to increase producers' incomes by optimizing energy resources.